Social Justice Across The English Curriculum In Indonesian Secondary Schools - Sugiono, Sugiono (International Journal of English Education and Linguistics (IJoEEL), 2020)
Social justice across curriculum is believed to entail changes in society, and thus the integration of social justice into curriculum comes to be crucial. Socially just curriculum deals with the principles of inclusive practices at schools, access to important knowledge and skills to all students, and the empowerment of students to act for socially just change. The purpose of this study was to investigate the extent to which the English curriculum in Indonesian secondary schools, year 10, is socially just.  This study focused on documentary research, analysing the collected documents – the curriculum framework and school-based curriculum development – from the lens of socially just curriculum indicators. These indicators were constructed based on the state ideology, Pancasila (Five Principles) and prominent scholars’ viewpoints of social justice covered in relevant literature.  The results showed that most of all, those documents reflected the indicators for socially just curriculum. Nevertheless, to make a judgment as to whether the English curriculum is socially just is not a simple matter, since further research, which promotes talks with teachers and students, observation of classroom activities, analysis of methods of assessment, student textbooks, workbooks, and other resources, would be necessary to be done.